Time Window Characteristics in a Heuristic Algorithm for a Full-Truck Vehicle Routing Heuristic Algorithm in An Intermodal Context - Wisute Ongcunaruk; Pornthipa Ongkunaruk; Gerrit Janssens (Jurnal Optimasi Sistem Industri)
Intermodal container terminals handle both the pickup and delivery of containers to and from customers, with these transport activities and terminal handling comprising a significant portion of intermodal transport costs. Efficient operations are therefore essential, particularly when time window constraints limit routing flexibility. This study presents a metaheuristic incorporating time windows to plan container pickups and deliveries. The proposed algorithm operates in three phases: initial solution construction using an insertion heuristic, improvement via local search, and further refinement through a deterministic annealing metaheuristic. The presence of time windows makes the planning more difficult, as the transport company has less flexibility in constructing the transport routes and, as a result, the distance travelled and/or the cost is increased. To assess how time window characteristics affect algorithm performance and cost, the study introduces two temporal descriptors—concentration (the clustering of time windows during the day) and specialization (the dominance of short or long-time windows in specific periods). The results of the experimental runs of the algorithm are statistically analysed to identify under which conditions of concentration and specialization an effect on the cost can be identified. Experimental results reveal that increased concentration leads to a rise in both the number of routes (up to 35%) and total cost (around 2%). While concentration results in more routes, these routes remain relatively cost-efficient. Furthermore, a lack of specialization in concentrated time windows amplifies both the number of routes and the total cost. Finally, the length of time windows influences these effects, with shorter time windows having a reduced impact on concentration and specialization outcomes compared to longer ones.